Transformações da notícia na imprensa do interior do Rio Grande do Sul : análise da Gazeta de Alegrete (1938-1968) - Schaedler, Cândida (2018)
Our dissertation aims at filling a gap in the study of the history of the interior newspapers. With the focus at the Gazeta de Alegrete, from Alegrete – the oldest newspaper from Rio Grande do Sul that is still circulating -, we show the news transformations, in the interior journalism from Rio Grande do Sul. Through the methodology of content analysis, proposed by Laurence Bardin (2009), and the categories event, news-values, journalism techniques, source, heard and quoted sources and framing, we analyzed 36 published headlines, between 1938 and 1968, in the newspaper. We also added History contributions to the study of Theories of Journalism, represented by Barbosa (2005) and Luca (2005). The sample is composed by the analysis of a copy in the months of March, June, September and December, in the years 1938, 1942, 1946, 1950, 1954, 1957, 1960, 1964 and 1968. Thus, we check the criteria for selection of the news, as well as its final presentation, with the objective of understanding the relations between journalism and politics in the period, since the Gazeta de Alegrete was aligned, first, with the Republican Party and then, to the Liberating Party. We noticed that, even with the political positioning and not being exempt from national and state debates, Gazeta do Alegrete always prioritized the local news, through news value of proximity, did a non-declaratory journalism and framed the news according to the interests of the party it supported - except at times when it was prevented by censorship. Nevertheless, it provided a service to the population of Alegrete, valuing the events of the city and region. The newspaper also followed the national journalistic changes, represented by the introduction of the lead and the inverted pyramid, although, in essence, it was still difficult to dissociate information and opinion.